2014
DOI: 10.1177/0957154x14544262
|View full text |Cite
|
Sign up to set email alerts
|

‘An atmosphere of cure’: Frederick Mott, shell shock and the Maudsley

Abstract: Although recognized as a medical scientist, the work of Frederick Mott as a physician, educator and clinical policymaker has been overshadowed. As a late entrant to the asylum system, Mott questioned established practices of treating mentally-ill patients and campaigned for reform. During World War I, entrusted with the management of the Maudsley neurological section, he sought to raise clinical standards and experimented with a range of therapies designed to treat the most severe or intractable forms of shell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…He dedicated his time during World War I to the investigation and treatment of shell-shock and was widely considered a leading figure in the field. 27 In 1918, he declared that 'in the majority of cases [of shell-shock] there is no evidence of commotional shock or concussion'. 28 The 1922 War Office enquiry into shell-shock found that soldiers with 'concussion shock' made up only 5-10% of all shell-shock cases.…”
Section: Confusing Termsmentioning
confidence: 99%
“…He dedicated his time during World War I to the investigation and treatment of shell-shock and was widely considered a leading figure in the field. 27 In 1918, he declared that 'in the majority of cases [of shell-shock] there is no evidence of commotional shock or concussion'. 28 The 1922 War Office enquiry into shell-shock found that soldiers with 'concussion shock' made up only 5-10% of all shell-shock cases.…”
Section: Confusing Termsmentioning
confidence: 99%
“…Frederick Mott, author of the term 'atmosphere of cure', introduced carpentry classes, choral singing, social events and turned the Maudsley Hospital grounds into a market garden with a poultry house to supplement the War Offi ce diet. 23 Psychological therapy was also practised at Seale Hayne under Hurst. Dr RG Gordon, a physician who subsequently practised as a neurologist took a particular interest in psychotherapy noting, 'there are certain of these cases which prove abnormally resistant to the ordinary methods of persuasion and suggestion, and in these a straightening out of the mental attitude may be of great assistance'.…”
Section: The Treatment Techniques Of Hurst -Rehabilitationmentioning
confidence: 99%
“…Such studies tend to present the relationship of the wounded and disabled men, the ‘poor brave souls’ of charitable campaigns (Cohen 2001 , 101–148), with wartime medicine as either an effeminizing or infantilising one (Jones 2014 , 417). The shell shock sufferers of Showalter’s analysis ‘were silenced and immobilized [by war] and forced, like women, to express their conflicts through the body.’ (Showalter 1987 , 171).…”
Section: War Medicine and Gendermentioning
confidence: 99%